2010
DOI: 10.1007/s12192-010-0212-z
|View full text |Cite
|
Sign up to set email alerts
|

αB-Crystallin inhibits the cell toxicity associated with amyloid fibril formation by κ-casein and the amyloid-β peptide

Abstract: Amyloid fibril formation is associated with diseases such as Alzheimer's, Parkinson's, and prion diseases. Inhibition of amyloid fibril formation by molecular chaperone proteins, such as the small heat-shock protein αB-crystallin, may play a protective role in preventing the toxicity associated with this form of protein misfolding. Reduced and carboxymethylated κ-casein (RCMκ-CN), a protein derived from milk, readily and reproducibly forms fibrils at physiological temperature and pH. We investigated the toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 63 publications
(124 reference statements)
7
57
0
1
Order By: Relevance
“…Moreover, α S1 -and β-CN can also prevent the formation of fibrillar structures by target proteins, including α S2 -and κ-CN (Thorn et al, 2005, ovalbumin (Khodarahmi et al, 2008), and amyloid-β peptide (Carrotta et al, 2012). Fibril formation by κ-CN is cytotoxic to PC-12 cells grown in culture but the effects are inhibited by α S -or β-CN (Dehle et al, 2010). More recently, it has been shown that α S2 -CN is also toxic to PC-12 cells and the neuronal cell line SH-SY5Y [Kegomoditswe Regoeng (University of Adelaide, Australia), John A.…”
Section: The Chaperone Action Of Caseinsmentioning
confidence: 99%
“…Moreover, α S1 -and β-CN can also prevent the formation of fibrillar structures by target proteins, including α S2 -and κ-CN (Thorn et al, 2005, ovalbumin (Khodarahmi et al, 2008), and amyloid-β peptide (Carrotta et al, 2012). Fibril formation by κ-CN is cytotoxic to PC-12 cells grown in culture but the effects are inhibited by α S -or β-CN (Dehle et al, 2010). More recently, it has been shown that α S2 -CN is also toxic to PC-12 cells and the neuronal cell line SH-SY5Y [Kegomoditswe Regoeng (University of Adelaide, Australia), John A.…”
Section: The Chaperone Action Of Caseinsmentioning
confidence: 99%
“…The level of Bc expression in brains of patients suffering AD is markedly increased compared to that in the normal human brain [105,186] presumably due to the cellular stress caused by disease. We and others have shown that aggregation of A and its associated cellular toxicity is prevented by Bc [187] or its isolated ACD [18] and thus sHsp overexpression in the context of AD may be as a protective mechanism. Fändrich et al have shown that there is an intracellular component to the aggregation and pathogenic nature of A which may explain the presence of Bc in the extracellular plaques of AD [188].…”
Section: The Role Of Shsps In Neurodegenerative Diseasementioning
confidence: 99%
“…Each treatment had six replicates. After a further 48 h of incubation, the treated cells were tested for viability by the MTT assay [29] using a BMG Polarstar microplate reader (BMG Labtechnologies, Germany). The results of the MTT assay were statistically analysed using one-way analysis of variance (ANOVA) followed by a Dunnett's comparison test (GraphPad PRISM V6).…”
Section: Methyl Tetrazolium Bromide Assaymentioning
confidence: 99%